Análisis de la cartera de microcrédito de las Cooperativas de Ahorro y Crédito de la ciudad de Loja, periodo 2020-2022 - Vega López, Michelle Johanna (2023)
Microcredit has emerged as a fundamental tool to support the country's development, reducing unemployment and underemployment rates. Savings and credit cooperatives, guided by the principles of cooperativism, collaboration and financial inclusion in all sectors of the population, have provided the necessary tools to promote social welfare through this inclusion. The present research aims to analyze the microcredit portfolio of Savings and Credit Cooperatives belonging to segments one and two in the city of Loja during the period 2020- 2022. The methodology used was mixed, combining quantitative and qualitative approaches. On the quantitative side, a simple linear regression econometric model was used to determine the relationship between levels of delinquency, liquidity and economic and financial profitability; on the qualitative side, interviews were conducted with credit union loan officers, allowing for a thorough internal evaluation. This study adopts a longitudinal design, examining four credit unions of Lojano origin that meet the necessary requirements for the research. The financial information was compiled from the website of the Superintendencia de Economía Popular y Solidaria. The main results reveal that the savings and credit cooperatives in segments one and two maintain a low level of concentration in microcredit, with consumer credit standing out as the main line of placement, although some cooperatives, such as CACEL and CACPE, manage to maintain low levels of delinquency below the limit required by the SEPS, others, such as CoopMego, face challenges with higher delinquency. The variety in portfolio composition between consumer and microcredit is evidence of the need for customized strategies to strengthen credit management and improve the financial health of the cooperatives under study.